Determinants Influencing Economic Growth in Five Asean Countries during The Period 2015-2024 - Ravakalista, Radista; Setyowati, Eni (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Economic development in the ASEAN region is shaped by complex dynamics arising from globalization, market volatility, and external influences. Guided by the endogenous growth theory, this study examines the impact of foreign direct investment (FDI), exchange rate fluctuations, inflation, and net exports on economic growth. Using panel data from five ASEAN countries Indonesia,Singapore, Thailand, Vietnam, and Brunei Darussalam covering the period 2015 to 2024, panel data regression analysis was employed. The results reveal that exchange rate stability and moderate inflation have a positive and significant effect on economic growth, whereas FDI and net exports are not statistically significant. These findings underscore the importance of maintaining monetary stability and adaptive economic governance to foster inclusive and sustainable growth in the ASEAN region.